Modernisation measuring of organization and activity of organs of state administration culture - Ігнатченко, І. Г. (Problems of legality, 2013)
The necessity of modernisation is grounded by state managements in the field of culture taking into account home and foreign experience. The special attention is sanctified to the search of ways of optimization of processes of forming and realization of public policy in the investigated area.